Osler-Weber-Rendu Disease Uncovered by Preeclampsia in a Case Report - Jamal Ouachaou; Hamza Mimouni; Mohammed Maarad; Yassine Mellagui; Asmae Oulad Amar; Houssam Bkiyar; Imane Kamaoui; Brahim Housni (Hindawi Limited, 2020)
Osler-Weber-Rendu disease (OWRD), called hereditary hemorrhagic telangiectasia, is an uncommon genetic illness with the dominant autosomal transmission. It cannot be easily or quickly diagnosed because of both its infrequency and its various associated symptoms. As far as its symptoms are concerned, the patient experiences recurring epistaxis, mucocutaneous telangiectasia, and arteriovenous malformations that can lead to severe undesirable symptoms. In our case, we report a 32-year-old female that was diagnosed with postpartum preeclampsia and whose paraclinical examinations showed that she suffers from hereditary hemorrhagic telangiectasia disease. Management of OWRD includes systematic diagnosis of visceral arteriovenous malformations (AVMs) in regular intervals, measures to prevent complications, and symptomatic treatment.